Mineralogical classification and impact simulation of the Punggur (H7-Melt Breccia) Meteorite, Indonesia - Muztaba, Robiatul; Danni Gathot Harbowo; Hakim Luthfi Malasan (Journal of Natural Sciences and Mathematics Research, 2025)
Meteorite falls in Indonesia are rarely examined through systematic scientific analysis, resulting in limited documentation of fall events and incomplete classification of recovered specimens. The Punggur meteorite fall of 28 January 2021 reportedly produced at least five fragments. This study addresses that gap by analyzing two fragments (PM-01 and PM-02) to confirm their extraterrestrial origin and to characterize their physical, chemical, and mineralogical properties. Physical characterization involved measurements of density, magnetic susceptibility, and surface morphology. The chemical composition was determined using X-ray fluorescence (XRF), while microscopic imaging was employed to compare fusion-crust features with interior textures. A web-based meteoroid-impact modeling tool was further employed to estimate the atmospheric entry behavior and environmental effects of the fall. The result is that PM-01 has dimensions of 13 × 6.5 × 8 cm, a volume of 419 mL, a mass of 2200 g, and a density of 5.25 ± 0.26 g/cm³. PM-02 measures 25 × 23 × 16 cm, with a volume of 443 mL, a mass of 1820 g, and a density of 4.06 ± 0.06 g cm⁻³. Modeling results indicate that post-airburst fragments retained a residual velocity of approximately 16.2 km s⁻¹, while the airburst released an estimated 2.12 × 10¹⁰ J of energy (0.51 × 10⁻⁵ megatons). The shock wave reached observers 1.78 minutes after the event, accompanied by a maximum wind velocity of 0.0422 m s⁻¹ and sound levels near 25 dB—consistent with witness reports and the observed impact crater. Microscopic and XRF analyses reveal coarse-grained textures with high concentrations of Fe, Si, and Mg. PM-01 contains 23.55% Fe, 20.18% Si, and 12.48% Mg, whereas PM-02 contains 48.09% Fe, 25.06% Si, and 10.21% Mg. Thus, this finding indicates that the specimen’s mineralogy is dominated by olivine ((Mg, Fe)₂SiO₄), confirming that it aligns with the classification of an H7 melt breccia.